1977
DOI: 10.1007/bf00232822
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-like cells of the pulmonary epithelium of the human adult lung

Abstract: The morphological and histochemical characteristics of endocrine-like cells of the pulmonary epithelium of the right lower lobe of 12 human adult lungs were studied. Few cells were reactive to the argyrophil silver method of Grimelius and of Sevier and Munger and cells with a similar morphology and distribution emitted a green or yellow fluorescence after treatment of the lung epithelium with the amine presursors L-DOPA or L-HTP, respectively. A greater number of cells seems to be demonstrated by electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 18 publications
1
19
1
1
Order By: Relevance
“…Histochemical studies suggest that dopamine is produced by decarboxylation of ¬_DOPA (l-3,4-dihydroxyphenylalanine) by the cells of the internal neuroendocrine system of the lungs (Cutz et al 1974;Hage, 1976;Scheuermann, 1991). This system, which has many similarities to the adrenal medulla, is both activated and at its maximal development at birth (Scheuermann, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histochemical studies suggest that dopamine is produced by decarboxylation of ¬_DOPA (l-3,4-dihydroxyphenylalanine) by the cells of the internal neuroendocrine system of the lungs (Cutz et al 1974;Hage, 1976;Scheuermann, 1991). This system, which has many similarities to the adrenal medulla, is both activated and at its maximal development at birth (Scheuermann, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This system, which has many similarities to the adrenal medulla, is both activated and at its maximal development at birth (Scheuermann, 1991). In the human, these neuroendocrine cells can be seen throughout the second half of gestation; they appear to reach their greatest development at or near delivery, and then decline in the months after birth (Hage, 1976;Johnson et al 1982). The same system is seen in guinea-pigs, mice and rabbits, but in the rabbit a number of independent studies have shown a dramatic but temporary loss of amine fluorescence just prior to birth (Hage, 1976;Sorokin et al 1982;Redick & Hung, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on normal adult human lung have noted a few immunoreactive neuroendocrine cells (55,56,115,116), which are located mainly in the terminal airways (115, 116). However, specimens from segmental resections for bronchiectasis with and without associated emphysematous changes (54) have shown an increase in solitary bronchial neuroendocrine cells and, along with specimens from patients with pulmonary fibrosis (115,116), have shown areas of focal and linear neuroendocrine hyperplasia.…”
Section: Sources Of 5-ht Within the Pulmonary Systemmentioning
confidence: 99%
“…Both light and electron microscopic studies have shown that K cells are usually flask-, oval-or pyramidalshaped with most of the cytoplasm concentrated at the base of the cells next to the basal lamina (10,15,22,25,48,58,93,94). Occasionally, lateral dendritelike cytoplasmic processes extend between nearby epithelial cells (10,13,15,94).…”
Section: Morphologymentioning
confidence: 99%